(untitled) (Sosio Konsepsia: Jurnal Penelitian dan Pengembangan Kesejahteraan Sosial, 2018)
In social work, spirituality is understood around the search of meaning, life purpose, transcendence, and connectedness. Connection with all of being out of the self is one of the research findings on the older adults’ spirituality. This research explored how the elders live spirituality which is expressed partly through the way they respond life experiences and sufferings. In addition, the exploration was also steered to understand how the elders’ spirituality contributes to their well-being. This qualitative study recruited eleven older persons as beneficiaries of institutional and home care social services. NVivo software was used to help to analyze data and to manage the coding results in a simple manner. The theme connectedness is reflected by some elements ranging from relationships, intimacy, isolation, to prayer. These elements have significant impact in shaping the elderly well-being. As the research implication, integrating spirituality into social work theory can be represented by the theme connectedness, that is by broadening the concept of person and environment in the person-in-environment theory.